Efficient Production of High Specific Activity Thulium-167 at Paul Scherrer Institute and CERN-MEDICIS - Heinke, Reinhard; Chevallay, Eric; Chrysalidis, Katerina; Cocolios, Thomas E.; Duchemin, Charlotte; Fedosseev, Valentin N.; Hurier, Sophie; Lambert, Laura; Leenders, Benji; Marsh, Bruce A.; van der Meulen, Nicholas P.; Sprung, Peter; et al. (Frontiers in Medicine, 2021)
Thulium-167 is a promising radionuclide for nuclear medicine applications with potential use for both diagnostics and therapy ("theragnostics") in disseminated tumor cells and small metastases, due to suitable gamma-line as well as conversion/Auger electron energies. However, adequate delivery methods are yet to be developed and accompanying radiobiological effects to be investigated, demanding the availability of Tm-167 in appropriate activities and quality. We report herein on the production of radionuclidically pure Tm-167 from proton-irradiated natural erbium oxide targets at a cyclotron and subsequent ion beam mass separation at the CERN-MEDICIS facility, with a particular focus on the process efficiency. Development of the mass separation process with studies on stable Tm-169 yielded 65 % and 60 % for pure and erbium-excess samples. An enhancement factor of thulium ion beam over that of erbium of up to several 10^4 was shown by utilizing laser resonance ionization and exploiting differences in their vapor pressures. Three Tm-167 samples produced at the IP2 irradiation station, receiving 22.8 MeV protons from Injector II at Paul Scherrer Institute (PSI), were mass separated with collected radionuclide efficiencies between 11 and 20 %. Ion beam sputtering from the collection foils was identified as a limiting factor. In-situ gamma-measurements showed that up to 45 % separation efficiency could be fully collected if these limits are overcome. Comparative analyses show possible neighboring mass suppression factors of more than 1000, and overall Tm-167/Er purity increase in the same range. Both the actual achieved collection and separation efficiencies present the highest values for the mass separation of external radionuclide sources at MEDICIS to date.